Brand Premium How Smart Brands Make More Money - Hollis, N. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Why do consumers pay a premium price for a brand? Is it better quality, the look and feel, or is it the brand's social standing? Author Nigel Hollis believes the answer to all those questions is "yes." Yet the vast majority of brands today trade on past equity and transient buzz. And marketers focus on plan execution rather than creating meaningful differentiation rooted in the brand experience. This lack of meaning is creating a market full of commodities rather than products that instill loyalty. But loyalty (i.e., repeat business) is the key to long term success, and that requires focusing on meaningful differentiation: functional, emotional, or societal. Here, brand expert Nigel Hollis focuses on the four components of a meaningfully different brand: purpose, delivery, resonance, and difference.This unique model will be applied to two very different brand models: premium priced and value priced. The models will show readers how to amplify what their brand stands for across all the brand touch points including: findability, affordability, credibility, vitality, and extendibility. The book will include cases of global brands such as Dyson, Johnnie Walker, Geico, Volkswagen, and more.